Edmodo, social network as a model for knowledge management - Augusto José Ángel Moreno, Flor Nancy Díaz Piraquive, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today's world both the Internet and ICT play a crucial role in all aspects of society. With the development of social networks, the way of communicating has changed, and this does not exclude educational environments. In the framework of e-learning, educational social networks have emerged as a tool that allows overcoming spatial and temporal barriers. A knowledge management model was applied to students in the programming area of three private universities in Bogota, Colombia, taking a sample of 76 students, from which an experimental group and a control group were taken, quantitative evaluations were made of aspects such as student participation and academic performance, in addition to a qualitative assessment of the model that was applied to students and teachers of the experimental group. It is observed that the model improves both group and individual participation, as well as academic performance, facilitating also the execution of the program in the established time and making communication between students and teachers more fluid. The conclusions allow to know that the model is superior to the traditional model and widely accepted by both students and teachers.